2020
DOI: 10.1002/anie.201914654
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Incorporation of Aromatic Oligoamides as Peptide Sidechain Appendages

Abstract: Derivatives of 4‐aminomethyl‐l‐phenylalanine with aromatic oligoamide foldamers as sidechain appendages were successfully charged on tRNA by means of flexizymes. Their subsequent incorporation both at the C‐terminus of, and within, peptide sequences by the ribosome, was demonstrated. These results expand the registry of chemical structures tolerated by the ribosome to sidechains significantly larger and more structurally defined than previously demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…3 Recently, it was shown that ribosomal translation tolerates peptide appendages consisting of aromatic amide foldamer sequences of quinoline-based monomer Q Xxx and pyridinebased monomer P (Figure 1a). [4][5][6] These appendages are far larger and more remote from peptides than what had been previously envisaged. They can be placed either at the Nterminus, i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 Recently, it was shown that ribosomal translation tolerates peptide appendages consisting of aromatic amide foldamer sequences of quinoline-based monomer Q Xxx and pyridinebased monomer P (Figure 1a). [4][5][6] These appendages are far larger and more remote from peptides than what had been previously envisaged. They can be placed either at the Nterminus, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…on the peptide chain initiator, 4,5 or within the sequence on an -amino acid side chain. 6 They can also be included within thioether peptide macrocycles such as 3 (Figure 1b). Interest for such peptide modifications stems from the high propensity of Q Xxx /P sequences to adopt stable helically folded conformations, particularly in water.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent study, four chemically diverse non-canonical scaffolds (phenylalanine, benzoic acid, heteroaromatic, and aliphatic acid analogs) were investigated for the compatibility of their substrates with the three flexizymes (Lee et al, 2019). Based on the molecular characteristics and yields in Fx-catalyzed reaction in several studies (Lee et al, 2021(Lee et al, , 2020b(Lee et al, , 2019(Lee et al, , 2020cPassioura and Suga, 2014;Rogers et al, 2018;Tsiamantas et al, 2020), several general substrate design rules were identified for efficient tRNA charging (Figure 4E). First, substrates with a similar molecular structure to…”
Section: Genetic Code Reprograming In Vitromentioning
confidence: 99%
“…Taken together, numerous non-canonical substrates have now been acylated to tRNA by Fx and subsequently incorporated site-specifically into a peptide in a reconstituted PURE system. The substrates include a- (Obexer et al, 2017), b-(Fujino et al, 2016, g- (Ohshiro et al, 2011), D-amino acids (Katoh et al, 2017) Review (Lee et al, 2021), non-amino (aromatic, aliphatic) acids (Lee et al, 2019), foldamers Rogers et al, 2018), oligomeric peptides (Tsiamantas et al, 2020), malonyl (polyketide-like) acids (Ad et al, 2019), hydroxyacids (Ohta et al, 2007(Ohta et al, , 2008, and thioacids (Takatsuji et al, 2019).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation